Mechanical-strength characteristics of concrete made with stainless steel industry wastes as binders. - Parrón-Rubio, María Eugenia; Barnett, Stephanie J.; Pérez-García, Francisca; Rubio Cintas, María Dolores (Elsevier, 2019)
One of the problems of steelworks, referring to the steel manufacture, is the generation of secondary products, resulting in recent years in new types of industrial waste that, depending on the sustainability of the environment, must be reused or treated. This paper analyzes the mechanical behavior of concrete samples with the addition of an industrial waste, such as ferritic fume dust produced by electric arc furnaces (EAF) when the materials are melted and makes a comparison using other types of additions of concrete such us silica fume. At the same time this paper studies the capacity of the matrix to encapsulate this residue that eventually ends up deposited in a landfill. The results show that, besides giving the concrete a greater resistance as it happens with silica fume, the use of this type of waste as an addition to concrete is suitable since the material remains encapsulated in the concrete matrix, thus not producing leaching of heavy metals which can be harmful to the environment and therefore to the health of the human being.
https://openpolicyfinder.jisc.ac.uk/id/publication/13693
Keywords: Hormigón; Acero inoxidable; Concrete; Fume dust EAF; Compressive strength; Flexural strength